2021
DOI: 10.3390/agriculture11100987
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbiome Regulates the Growth of Mustard under Organic Greenhouse Cultivation

Abstract: Organic cultivation can improve soil fertility and biodiversity through the preservation of soil organic matter. Meanwhile, greenhouse cultivation can provide a controlled environment and therefore enables the management of every aspect of plant growth. In recent years, the combination of organic and greenhouse cultivation has slowly become a popular option in tropical regions to prevent the unpredictable impact of weather. Although it is known that organic cultivation significantly increases the density and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…[ 52 ]. Liu et al [ 53 ] indicated that Dyella could improve mustard’s growth under greenhouse conditions; the present study showed that Dyella abundance might be linked to the best PGP effects on hybrid Pennisetum under greenhouse conditions through a positive association with pp02. Pseudomonas is among the major PGP halotolerant bacteria, which positively affected plant growth for their ability to supply phosphorus to plants, act as phytohormones to stimulate plant development, chelate and absorb iron through siderophores, and reduce the intermediate to ethylene (plant stress hormone) [ 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…[ 52 ]. Liu et al [ 53 ] indicated that Dyella could improve mustard’s growth under greenhouse conditions; the present study showed that Dyella abundance might be linked to the best PGP effects on hybrid Pennisetum under greenhouse conditions through a positive association with pp02. Pseudomonas is among the major PGP halotolerant bacteria, which positively affected plant growth for their ability to supply phosphorus to plants, act as phytohormones to stimulate plant development, chelate and absorb iron through siderophores, and reduce the intermediate to ethylene (plant stress hormone) [ 54 , 55 , 56 , 57 ].…”
Section: Discussionsupporting
confidence: 52%
“…Dyella also showed PGP activities in Phaseolus vulgaris and Lespedeza sp. [52]. Liu et al [53] indicated that Dyella could improve mustard's growth under greenhouse conditions; the present study showed that Dyella abundance might be linked to the best PGP effects on hybrid Pennisetum under greenhouse conditions through a positive association with pp02.…”
Section: Discussionsupporting
confidence: 52%
“…This plant will grow quickly if planted with the right humidity. Thus, this plant is suitable for cultivation at the end of the rainy season (Liu et al, 2021). According to (Ahemad & Khan, 2012), the cultivation of mustard plants in planting media must be fertile.…”
Section: Introductionmentioning
confidence: 99%
“…This plant will grow quickly if planted with the right humidity. Thus, this plant is suitable for cultivation at the end of the rainy season (Liu et al, 2021). According to (Ahemad & Khan, 2012), the cultivation of mustard plants in planting media must be fertile.…”
Section: Introductionmentioning
confidence: 99%